Emerging MXenes for Functional Memories. Issue 9 (5th May 2021) - Gong, Yue; Xing, Xuechao; Wang, Yan; Lv, Ziyu; Zhou, Ye; Han, Su-Ting
Abstract : MXenes are a rapidly growing family of 2D materials. The composition, morphology, structure, surface chemistry, and structural configuration of MXenes directly affect their electrochemical performance. For example, when used as the source and drain electrodes in a transistor, MXenes provide increased chemically active interfaces, reduced ion diffusion length, and improved inplane carrier/charge transport kinetics, thus improving the storage performance of the transistor significantly. The work function and bandgap of MXenes can be controlled by tailoring their structure and surface functional groups. This makes MXenes as the first choice for several storage applications. Herein, the latest progress in the synthesis and properties of MXenes is summarized, and it is aimed to boost the motivation of researchers for developing novel MXenes and improving their applications. It emphasizes on the importance of MXenes in high‐density data storage applications, such as flash memories and memristors. The applications of MXenes in artificial synapses, neurons, and logic circuits are also discussed. A future roadmap is outlined for realizing the storage applications of MXenes. Abstract : The latest progress in the synthesis and properties of MXenes is summarized. This review emphasizes on the importance of 2D MXenes in energy storage applications, including memristors and field‐effect transistor devices. The applications of MXenes in artificial synapses, neurons, and logic circuits are also discussed, which offers a potential roadmap for realizing the storage applications.